Determinant Audit Quality Moderated by Audit Committee - Rukmana Aryawiraraja Danatungga; Temy Setiawan; Kurniawati Kurniawati (SEAN Institute, 2026)
This study aims to analyze the effect of audit delay, audit rotation, and audit tenure on audit quality, with the audit committee as a moderating variable and firm size and leverage as control variables. This research employs a quantitative approach using secondary data in the form of annual reports of energy sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The sample was determined using purposive sampling, while data analysis was conducted using multiple linear regression and moderation testing with SPSS software. The results indicate that audit delay has a negative and significant effect on audit quality, suggesting that delays in auditing reduce audit quality. In contrast, audit rotation and audit tenure do not have a significant effect on audit quality. Furthermore, the audit committee was not found to moderate the relationship between the independent variables and audit quality. However, all variables in the model simultaneously have a significant effect on audit quality. These findings emphasize the importance of timeliness in the audit process and indicate that formal governance mechanisms are not necessarily effective in improving audit quality. This study has implications for companies, auditors, and regulators in enhancing the quality of financial reporting and the effectiveness of audit oversight